Uncovering the Triadic Relationship: IC, Profitability, and Sustainability Reporting in Southeast Asian Companies - Renata, Madeline; Marlina, Maria Asumpta Evi (International Business Management - Universitas Ciputra, 2026)
This study investigates the relationship between intellectual capital (IC), profitability, and sustainability reporting in companies within the agriculture and food and beverage (FnB) sectors across three major ASEAN countries: Indonesia, Thailand, and the Philippines. In light of the COVID-19 pandemic, the urgency for businesses to leverage intangible assets has intensified, as these assets are pivotal for maintaining resilience and achieving sustainable competitive advantages. By analyzing the components of intellectual capital—human capital efficiency (HCE), structural capital efficiency (SCE), relational capital efficiency (RCE), and capital employed efficiency (CEE)—this research aims to elucidate their impact on corporate profitability and the role of sustainability reporting in enhancing financial performance. The findings are expected to contribute to a more comprehensive framework for managing and communicating corporate value, thereby facilitating better decision-making for companies and investors. This study also highlights the similarities in economic development and accounting frameworks among the selected countries, which allows for relevant comparisons and enhances the generalizability of the results to other ASEAN nations with comparable characteristics. Ultimately, this research underscores the critical importance of intellectual capital in navigating economic uncertainties and fostering long-term business success.